2021
DOI: 10.1684/epd.2021.1273
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic data on brivaracetam, lacosamide and perampanel during pregnancy and lactation

Abstract: We present pharmacokinetic data during pregnancy and lactation for brivaracetam, lacosamide and perampanel based on two case studies. Patient 1 used brivaracetam as monotherapy and gave birth to twins. Patient 2 used a combination of brivaracetam, lacosamide and perampanel. In both patients, serum drug concentrations were monitored throughout the pregnancies. Drug concentrations were also analysed in umbilical cord blood at birth, in serum from the offspring and in breastmilk after five days and 3-11 weeks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…These findings stress the need in therapeutic drug monitoring of lacosamide levels in pregnant women, particularly because dose modifications may be required along pregnancy. A recent study demonstrated that the dose‐normalized concentrations of lacosamide were 40% lower during pregnancy as compared with postpartum levels, 27 similar to earlier observations 28,29 . In this context, our findings support therapeutic monitoring while adjusting lacosamide doses during pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…These findings stress the need in therapeutic drug monitoring of lacosamide levels in pregnant women, particularly because dose modifications may be required along pregnancy. A recent study demonstrated that the dose‐normalized concentrations of lacosamide were 40% lower during pregnancy as compared with postpartum levels, 27 similar to earlier observations 28,29 . In this context, our findings support therapeutic monitoring while adjusting lacosamide doses during pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“… 105 Serum concentrations of lacosamide in pregnancy remained fairly stable in a small study. 52 Whereas a decrease was reported in seven pregnancies (lacosamide 200–600 mg/day), through each trimester compared with the baseline without effect on seizure frequency; none of the neonates had MCMs. 106 However, more consistent data come from the recently published MONEAD (Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs) study, reporting a decrease of dose-normalized concentrations during pregnancy of 39.9% for lacosamide (26.14–15.71 μg/L/mg; p < 0.001).…”
Section: Management Of Epilepsy During Pregnancy and Anti-seizure Med...mentioning
confidence: 97%
“…A woman under brivaracetam in monotherapy and another under polytherapy with brivaracetam, lacosamide, and perampanel had only minor changes in concentration/dose ratios of brivaracetam. 52 The few data available are not sufficient to give clinical advice.…”
Section: Management Of Epilepsy During Pregnancy and Anti-seizure Med...mentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the incidence of AEs in children groups is lower than that in patients of all age groups. This was probably because that the number of included study of children was limited, eventhough previous studies have suggested a good level of efficacy and safety for LCM throughout pregnancy and breastfeeding and argue against teratogenic or toxic potentialities (Lattanzi et al, 2017;Maria et al, 2019); however, since LCM appears to cross the near-term placenta freely and could accumulate in a breastfed infant due to lower renal excretion, more studies are needed to identify the safety of LCM in pregnancy and newborn (Svendsen et al, 2017;Kohn et al, 2020;Landmark et al, 2021).…”
Section: Limitation and Future Researchmentioning
confidence: 99%